2021
DOI: 10.1002/rmv.2292
|View full text |Cite
|
Sign up to set email alerts
|

Cell death mechanisms involved in cell injury caused by SARS‐CoV‐2

Abstract: Coronavirus disease 2019 (Covid‐19) is an emerging novel respiratory infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) that rapidly spread worldwide. In addition to lung injury, Covid‐19 patients may develop extrapulmonary symptoms, including cardiac, liver, kidney, digestive tract, and neurological injuries. Angiotensin converting enzyme 2 is the major receptor for the entry of SARS‐CoV‐2 into host cells. The specific mechanisms that lead to cell death in different tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 151 publications
(299 reference statements)
2
21
0
Order By: Relevance
“…The exact mechanism of SARS-CoV-2 viral spread through the respiratory tract, kinetics of infection and cytokine release are still under investigation. Multiple studies using other coronaviruses [ 8 , 30 , 31 ] have attempted to help fill the gaps in our knowledge of COVID-19 disease pathogenesis. However, although SARS-CoV-2 is in the same Betacoronavirus clade as MERS-CoV and SARS-CoV, there are notable differences between their whole genome and amino acid sequences, with SARS-CoV-2 being closer related to bat coronaviruses than other viruses associated with outbreaks in humans [ 32 , 33 ].…”
Section: Coronaviruses Sars-cov-2 and Covid-19 Disease Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism of SARS-CoV-2 viral spread through the respiratory tract, kinetics of infection and cytokine release are still under investigation. Multiple studies using other coronaviruses [ 8 , 30 , 31 ] have attempted to help fill the gaps in our knowledge of COVID-19 disease pathogenesis. However, although SARS-CoV-2 is in the same Betacoronavirus clade as MERS-CoV and SARS-CoV, there are notable differences between their whole genome and amino acid sequences, with SARS-CoV-2 being closer related to bat coronaviruses than other viruses associated with outbreaks in humans [ 32 , 33 ].…”
Section: Coronaviruses Sars-cov-2 and Covid-19 Disease Pathologymentioning
confidence: 99%
“…Coronaviruses are known to engage apoptotic pathways via diverse mechanisms. The SARS-CoV accessory proteins ORFs 3a, 6, 7a, 7b, 8a and 9b, as well as the structural proteins M and N, were associated with apoptosis (reviewed in [ 8 ]), but their relevance during in vivo infection still needs to be clarified. Several studies addressing the role of viral proteins in cell death show they can lead to apoptosis through a variety of signaling events.…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The replication of coronaviruses in cells is regulated by many host factors, which can induce drastic structural and physiological changes in cells ( 2 ). During infection, SARS-CoV-2 could induce diverse cell death pathways ( 31 , 32 ), such as apoptosis, necroptosis, pyroptosis, and NETosis in the host cells ( Figure 1B ).…”
Section: Multiple Cell Death Pathways Were Induced In Sars-cov-2 Infe...mentioning
confidence: 99%
“…Recently in a published article in Reviews in Medical Virology , Morais da Silva et al., described the different mechanisms that are involved in cell death process such as apoptosis, autophagy, and necrosis which are caused by SARS‐CoV‐2. 1 The authors reported SARS‐CoV and SARS‐CoV‐2 genomes contain eight accessory genes whose open reading frames are interspersed among the structural genes; two between S and E genes (ORFs 3a and 3b), five are located between the M and N genes (6, 7a, 7b, 8a, 8b) and one within the N gene (9b); in addition, the authors presented ORF8a as one of the accessory proteins in both SARS‐CoV and SARS‐CoV‐2 in fig. 1, 1 although scientific evidence show that genome of SARS‐CoV‐2 lacks ORF8a.…”
mentioning
confidence: 99%